Novel Evanescent-Mode Cavity Filter With Reconfigurable Rat-Race Coupler, Quadrature Coupler and Multi-Pole Filtering Functions - Junchen Lai (IEEE Access, 2020)
A novel evanescent-mode cavity filter with multiple reconfigurable functions including filtering rat-race coupler, filtering quadrature coupler and multi-pole filtering is proposed in this paper. It simply consists of four substrate integrated waveguide (SIW) evanescent-mode cavity resonators which are arranged in a ring loop. By loading piezoelectric actuators on top of each resonator and inserting varactors between adjacent resonators, the structure can achieve multiple reconfigurable functions among filtering rat-race coupler, filtering quadrature coupler and single-ended multi-pole filters, in addition to continuously frequency, independent bandwidth, and power-division tuning. Measurement shows that the filtering quadrature coupler corves a frequency range of 2.08-3.00 GHz with insertion loss of 2.99 ± 0.31dB, while the filtering rat-race coupler corves a frequency range of 2.31-2.71 GHz with insertion loss of 2.97 ± 0.13dB; The single-ended filter can be switched among two-pole, three-pole, and four-pole with frequency range of 2.38 to 3.01 GHz, 2.47 to 3.08 GHz and 2.53 to 3.00 GHz, respectively. Good agreement is obtained between simulated and measured results.